Measuring the aesthetic elements of screen designs - Ngo, D (2001)
Given the critical role that screen aesthetics plays in human-computer interaction, it is important to understand what characteristics of screens influence user acceptance. The purpose of this paper is to present a set of screen characteristics that appear to be important determinants of acceptance, and to present the results of two experiments used to developed and validate a system for predicting user acceptance based on the screen characteristics. (C) 2001 Elsevier Science B.V. All rights reserved.